Factors Associated with the Time to the First Wheezing Episode in Infants: A Cross-Sectional Study from the International Study of Wheezing in Infants (Eisl) - Mallol-Villablanca, E (Nature Publishing Group, 2016)
Male gender, asthmatic heredity, perinatal tobacco smoke exposure and respiratory infections have been associated with wheeze in the first years of life, among other risk factors. However, information about what factors modify the time to the first episode of wheeze in infants is lacking. The present study analyses which factors are associated with shorter time to the first episode of wheeze in infants. Parents of 11-to 24-month-old children were surveyed when attending their health-care centres for a control visit. They answered a questionnaire including the age in months when a first wheeze episode (if any) had occurred (outcome variable). The study was performed in 14 centres in Latin America (LA) and in 8 centres in Europe (EU) (at least 1,000 infants per centre). Factors known to be associated with wheezing in the cohort were included in a survival analysis (Cox proportional hazards model). Summary hazard ratios adjusted for all risk factors (aHR) were calculated using the meta-analysis approach with random effects. A total of 15,067 infants had experienced wheezing at least once, out of 35,049 surveyed. Male gender in LA (aHR 1.05, 95% confidence interval (CI) 1.00-1.10, P=0.047), parental asthma in LA and EU (aHR 1.05, 95% CI 1.00-1.11, P=0.037), infant eczema in EU (aHR 1.25, 95% CI 1.12-1.39, P<0.001) and having a cold during the first 3 months in LA and EU (aHR 1.97, 95% CI 1.90-2.04, P<0.001), in LA (aHR 1.98, 95% CI 1.90-2.06, P<0.001) and in EU (aHR 1.91, 95% CI 1.75-2.09, P<0.001) were associated with a shorter period of time to the first episode. Breast feeding for at least 3 months was associated with a longer period, only in LA (aHR 0.91, 95% CI 0.86-0.96, P<0.001). Cold symptoms during the first 3 months is the most consistent factor shortening the time to the first episode of wheezing; breast feeding for 3/43 months delays it only in LA, whereas eczema shortens it only in EU. Avoiding a common cold in the first months of life could be a good strategy to delay the first wheeze episode; however, cohort studies will help to elucidate this association. © 2016 Primary Care Respiratory Society UK.